MOBILITY OF HEAVY METALS IN SELF-BURNING WASTE HEAPS OF THE ZINC SMELTING PLANT IN BELOVO (KEMEROVO REGION, RUSSIA) - Sidenko N.V.; Bortnikova S.B.; Pal'chik N.A.; Gieré R.; Cottard F. (My University, 2001)
Approximately 70,000 tons of slags, containing a high concentration of fine-grained carbon and heavy metals were accumulated in the town of Belovo (Kemerovo region, Russia) as a result of Zn-smelting between 1950 and 1994. Spontaneous ignition of fine-grained carbonaceous material and the subsequent burning of the waste heaps produced a zoning pattern which is characterized by three types of altered waste material: burned (or pyrometamorphic) waste, metamorphosed waste, and weakly altered waste. The self-combustion process is the reason for a redistribution of various elements. Leaching tests were carried out to understand the behavior of soluble (extracted by distilled water) and mobile (extracted by 1N HCl) metal forms; water analyses were performed using atomic absorption spectroscopy. The mobile metal species were accumulated close to the combustion center, in the burned and metamorphosed waste. In contrast to this, the soluble species were precipitated further away from the combustion center, on the surface of the waste heaps near active fumaroles, which provide evidence for ongoing combustion in the interior parts of the heaps. These observations are confirmed by mineralogical studies using routine mineralogical techniques: elementary copper and newly formed zincite and willemite are found in the burned and thermally metamorphosed waste, whereas soluble sulfates of Cu, Zn and Fe were deposited in the weakly altered zones near the surface of the waste heaps. The relative ability of the studied elements to migrate, determined as the proportion of the mobile or soluble to total metal concentrations, decreases in the order Cd>Zn>Cu>Pb>Fe for both the soluble and mobile forms. Primary metal-bearing waste material appears to be more resistant to weathering than the secondary phases formed as a result of combustion. Every hour, drainage waters remove about 3 kg Zn and 2 kg Cu from the waste heaps.